Postmodern Concepts in the Novel 'Gorashar' by Saydqader Hidayeti (Raparin Journal of Humanities (RJH), 2025)
This research, titled "Postmodern Concepts in the Novel 'Gorashar' by Saydqader Hidayeti," is an attempt to read the novel Gorashar under the light of postmodern critical theories. The content of this novel encompasses a collection of distinct postmodern foundations, as among the most prominent foundations of this critical movement are: minimalism, metafiction, pastiche, intertextuality, decentering, play, fragmentation, marginalization of grand narratives, paranoia, etc. From here, literature becomes a laboratory for practicing the postmodern critical movement, and has also become an important field for experimenting with the various effects of this critical trend. Therefore, those views that consider postmodernism as the creator of literary criticism are rejected. These postmodern concepts are rarely seen in Kurdish research, which is why we have conducted our research on this topic. We have benefited from the descriptive method under the light of postmodern theories. Our aim is to identify each of these foundations in the novel Gorashar. This research consists of an abstract, preface, two chapters, conclusion, and list of sources. Chapter One: Terms, concepts, definitions, and history of postmodernism. Chapter Two: concepts of postmodernism in the novel Gorashar.